On a conjecture of E.M. Stein on the Hilbert transform on vector fields - Lacey, Michael T. (Michael Thoreau) (Memoirs of the American Mathematical Society ;, 2010)
Hilbert transform -- Carleson Theorem -- Fourier series -- Kakeya set -- vector field -- Maximal Function -- phase plane.